Urgensi Perlindungan Kesehatan dan Keselamatan Pekerja Tambang Uranium dari Paparan Zat Radioaktif di Indonesia - Nugraha, Ryan Fitra; B, Budiarsih (Media Hukum Indonesia (MHI), 2025)
This study examines the legal protection of health and safety for uranium mine workers in Indonesia against radioactive exposure using a normative legal approach. The research is motivated by the potential long-term health risks posed by radiation in uranium mining, while national regulations are deemed incomplete and misaligned with international standards such as those set by the International Atomic Energy Agency (IAEA) and the International Labour Organization (ILO). The methodology involves analyzing national legal documents (Labor Law, BAPETEN Regulations) and international instruments (IAEA Conventions, ILO standards) to identify regulatory gaps. Findings reveal fragmentation in Indonesia’s legal framework, the absence of radiological protection specifications in labor laws, and weaknesses in implementing the ALARA (As Low As Reasonably Achievable) principle and radiation exposure limits. Additionally, the study highlights the lack of compensation mechanisms, legal safeguards for workers, and strict liability for companies. Recommendations include harmonizing national regulations with IAEA standards, drafting specialized regulations for uranium mining, establishing a dedicated inspectorate, enhancing human resource capacity through training, and allocating a minimum of 15% of operational budgets for radiation protection systems. The implications underscore the need to integrate technical, legal, and human rights aspects to ensure safe working environments and the sustainability of Indonesia’s nuclear industry. Lessons from countries like Canada and Australia demonstrate that investing in worker safety reduces health risks while boosting productivity and industrial sustainability. Holistically, protecting uranium miners transcends legal obligations, reflecting the state’s constitutional duty to guarantee citizens’ rights to safe workplaces. With the potential growth of the nuclear sector, Indonesia must urgently develop a comprehensive, evidence-based protection system rooted in social justice before commercial uranium mining operations commence.